Uji Efektivitas Ekstrak Daun Sirih (Piper betel l.) dalam Hand Sanitizer terhadap Aktivitas Bakteri Staphylococcus aureus - Go, Dinsella; Pakan, Prisca Deviani; Setianingrum, Elisabeth Levina Sari; Damanik, Efrisca M. Br. (Cendana Medical Journal, 2022)
The importance of self-hygiene needs to be taken seriously by everyone. Small habits such as washing hands can save and protect people from infectious diseases, mainly COVID-19. The usage of hand sanitizers can be another alternative in keeping one’s hands clean from germs and bacteria. This study will be utilizing piper leaf extract (Piper betel l.) as the main ingredient in hand sanitizer formulation.